(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the causes, types, approaches to education and upbringing, rehabilitation and correctional work, as well as recommendations based on the principles of family upbringing and the individual characteristics of the child. The article also provides specific practical recommendations for the formation of fine motor skills, sensory-emotional development and motor activity.